Malaria parasite detection in peripheral blood images - Tek, F. Boray; Dempster, Andrew G.; Kale, Izzet (British Machine Vision Association, BMVA, 2006)
This paper investigates the possibility of computerised diagnosis of malaria and describes a method to detect malaria parasites (Plasmodium spp) in images acquired from Giemsa-stained peripheral blood samples using conventional light microscopes. Prior to processing, the images are transformed to match a reference image colour characteristics. The parasite detector utilises a Bayesian pixel classifier to mark stained pixels. The class conditional probability density functions of the stained and the non-stained classes are estimated using the non-parametric histogram method. The stained pixels are further processed to extract features (histogram, Hu moments, relative shape measurements, colour auto-correlogram) for a parasite/non-parasite classifier. A distance weighted K-nearest neighbour classifier is trained with the extracted features and a detailed performance comparison is presented. Our method achieves 74% sensitivity, 98% specificity, 88% positive prediction, and 95% negative prediction values for the parasite detection.
2006 17th British Machine Vision Conference, BMVC 2006 --
Keywords: Bayesian; Blood images; Blood samples; Color characteristics; Image colours; Light microscopes; Malaria parasite; Peripheral blood; Reference image; Pixels